45.0k views
3 votes
If f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)

If f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)-example-1
User Agus
by
6.2k points

2 Answers

6 votes

(f - g)(x) = f(x) - g(x)

= 3x - 2 - 2x - 1

= x - 3

Thus athe answer is

User Talentedmrjones
by
6.2k points
5 votes

Answer:

A

Explanation:

note that (f - g)(x) = f(x) - g(x)

f(x) - g(x)

= 3x - 2 - (2x + 1) ← distribute by - 1

= 3x - 2 - 2x - 1 ← collect like terms

= x - 3 → A

User Cemregoksu
by
5.7k points